Operations Management / Second Edition - Chambers Stuart; Harland Christine; Harrison Alan; Johnson Robert; Slack Nigel (Financial Times - Pitman Publishing, 1998)
The book gives students a clear, well structured and comprehensive treatment of Operations Management. Introduction, Operations Management, The Strategic Role and Objectives of Operations, Operations Strategy, Design, Design in Operations Management, The Design of Products and Services, Design of the Operations Network, Layout and Flow, Process Technology, Job Designed Work Organization, Planning and Control, The Nature of Planning and Control, Capacity Planning and Control, Capacity Planning and Control, Inventory Planning and Control, Supply Chain Planning and Control, MRP, Just-in-Time Planning and Control, Project Planning and Control, Quality Planning and Control, Improvement, Operations Management, Failure Prevention and Recovery, Total Quality Management, The Operations Challenge, Appendices, Index.